Título Padrão: Registro de Ostrea puelchana d’Orbigny, 1842 (Bivalvia: Ostreidae), como novo epibionte em Eriphia gonagra (Fabricius, 1781) (Crustacea: Eriphiidae) para o Nordeste do Brasil - Alves-Júnior, Flavio Almeida; Lucatelli, Débora; Arruda Francisco, Jonata; Fabiano de Araújo Ferreira, Gledson; Fidelis de Souza-Filho, Jesser (Arquivos de Ciências do Mar, 2021)
In this paper, we describe the first association of the ostreid species Ostrea puelchana d’Orbigny, 1842, as new epibiont in Eriphia gonagra (Fabricius, 1781), with material collected in Northeastern Brazil. The specimens of E. gonagra were collected manually in November of 2020 during the low tide in the Barra de Catuama beach, State of Pernambuco. Among 10 specimens collected, only one adult male showed the presence of two commensal specimens of O. puelchana adhered in the epibranchial and antero-lateral regions of the basibiont (right side). The presence of the epibiont O. puelchana on the new host E. gonagra expands the range of the crustacean species potentially used as hosts by this oyster along the Brazilian coast. Keywords: marine invertebrates, biological interactions, Pernambuco, commensalism, beachrocks.